The Voice of the Century : The Culture of Italian Bel Canto in Luisa Tetrazzini's Recorded Interpretations. - Zicari, Massimo. (Open Book Publishers, 2022)
The fields of performance studies, empirical musicology, and the musicology of recordings have seen a tremendous development in recent years, shedding new light on the recent history of our performing tradition and conveying essential information to music practitioners, critics and audiences.This innovative work considers the notion of bel canto and the manner in which this vibrant tradition lives in the records of Luisa Tetrazzini (1871-1940), one of the most celebrated sopranos ever. Tetrazzini, whose discographic career includes about 120 recordings, belongs to that generation of inspirational performers who heralded the dawn of a new era of music appreciation, alongside such iconic figures as Enrico Caruso, Adelina Patti and Nellie Melba.